PENGARUH BAURAN PEMASARAN 7P TERHADAP LOYALITAS PELANGGAN PADA UMKM HESYA KITCHEN - Atika Mai Hesya, (2022)
This research is a quantitative research which has the aim to determine the effect of product, price, promotion, place, people, physical evidence and process on customer loyalty in Hesya Kitchen. In this study using Hesya Kitchen's customers as the research population and the sample used was 144 respondents. The data collection technique used is using a questionnaire using google form as a medium to obtain research data from respondents. The analytical tool used is SPSS 20. The research model uses validity and reliability tests and hypothesis tests using T-test and F-test. The results of this study are product, price, promotion, place, people, physical evidence and process have a significant effect on loyalty customer